2021
DOI: 10.1371/journal.pntd.0009200
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni alter transcription of immunomodulatory gene products following in vivo praziquantel exposure

Abstract: Control of the neglected tropical disease schistosomiasis relies almost entirely on praziquantel (PZQ) monotherapy. How PZQ clears parasite infections remains poorly understood. Many studies have examined the effects of PZQ on worms cultured in vitro, observing outcomes such as muscle contraction. However, conditions worms are exposed to in vivo may vary considerably from in vitro experiments given the short half-life of PZQ and the importance of host immune system engagement for drug efficacy in animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In this study, we demonstrate that in vivo exposure to PZQ induces significant changes in the expression of the worm's lncRNAs, even several hours after the treatment. In our re-analyses of the RNA-Seq data of McCusker et al [11], we found hundreds of lncRNAs differentially expressed both in mature and immature worms. Through RT-qPCR we validated the differential expression of selected lncRNAs, underscoring the impact of PZQ on altering S. mansoni lncRNA expression.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In this study, we demonstrate that in vivo exposure to PZQ induces significant changes in the expression of the worm's lncRNAs, even several hours after the treatment. In our re-analyses of the RNA-Seq data of McCusker et al [11], we found hundreds of lncRNAs differentially expressed both in mature and immature worms. Through RT-qPCR we validated the differential expression of selected lncRNAs, underscoring the impact of PZQ on altering S. mansoni lncRNA expression.…”
Section: Introductionmentioning
confidence: 57%
“…Nevertheless, worm response to this drug is still not fully understood since it depends on a complex disruption of the parasite homeostasis. This involves the host's immune system [1,6,7] in addition to the regulation of gene expression in the parasite when exposed to PZQ, as shown by McCusker et al [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…PZQ's lack of efficacy in immature worms may be a result of the need for involvement of the hosts' immune system since eggs are released by sexually mature worms and the host responds to their antigens with a wave of macrophage recruitment to the liver and an acute Th2 response [62], [63]. A study by McCusker et al reported that in vivo exposure to PZQ resulted in the alteration of the transcription gene products of S. mansoni [64].…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the number of eggs being excreted per adult worm present, changing with treatment. This could also be due to juvenile worms surviving treatment and continuing to regurgitate antigens but not yet producing eggs, or previously egg-producing adult worms surviving treatment but becoming - at the very least, temporarilysterilized (26) or otherwise unable to reproduce (27).…”
Section: Discussionmentioning
confidence: 99%